Magnitude and Reasons for Gaps in Tuberculosis Diagnostic Testing and Treatment Initiation: An Operational Research Study from Dakshina Kannada, South India - Imaad Mohammed Ismail; Akshaya Kibballi Madhukeshwar; Poonam Ramesh Naik; Badarudeen Mohammad Nayarmoole; Srinath Satyanarayana (Springer, 2020)
Background: In India, ensuring all Persons with Presumptive TB (PPTB) undergo TB diagnostic tests and initiating all diagnosed TB patients on treatment are two major implementation challenges. Objectives: In a coastal district of Karnataka state, South India, to (1) determine the number and proportion of PPTB who did not undergo any TB diagnostic test, and the number and proportion of TB patients who were not initiated on treatment (2) explore the facilitators and barriers in TB diagnostic testing and treatment initiation from health care providers' perspective. Methods: For objective-1, we used a cross-sectional design involving review of data of PPTB enrolled for care during January-March 2019 and for objective-2, we used a qualitative design involving key informant interviews of health care providers. Results: Of 8822 PPTB patients enrolled for evaluation of TB, 767 (9%) had not undergone any TB diagnostic test. In those who had undergone any TB diagnostic test, a total of 822 were diagnosed with TB and of them, 26 (3%) were not initiated on treatment. Cartridge-based nucleic acid amplification tests was used as a diagnostic test only among 1188 (13.5%) PPTB patients. The gaps in diagnostic testing were due to: non-availability of doctors/lab-technicians, inadequate knowledge about TB diagnostic tests among health care providers, reluctance of patients to undergo the TB diagnostic tests due to stigma/confidentiality issues and sub-optimal engagement of private health facilities for TB control. Conclusion: About 9% of PPTB not undergoing any test for TB and 3% of the TB patients not initiated on treatment are of major concern. Revised National TB Control Programme needs to address the identified barriers to improve the process of TB diagnosis and treatment initiation.